The perceptions and experiences of employed fathers on paternity leave - Tladi, Nkatane (My University, 2017)
The South African workforce has been transforming over centuries. Post -1994 South Africa brought about liberal changes in labour laws and policies, which saw women getting a four months maternity leave but there was a shortfall when it came to fathers in the workplace. The laws are mute about the father’s time off during birth of the child; the only provision made is the three days family responsibility leave. The purpose of this research was to explore the perceptions and experiences of fathers with regard to the absence of paternity leave in the legislation and their experiences in early child care with new-borns. The study used a qualitative strategy and a case study design to better understand the perceptions and experiences of employed fathers. A purposive and convenience sampling procedure were used, with a sample of 15 fathers with reproductive age ranging from 25 to 55. The fathers that were interviewed came from three different companies, where a semi structured interview was employed to collect data. Data was analysed using thematic analysis that allowed the researcher to identify the recurring themes. The findings of the study demonstrated a need for paternity leave to allow fathers to be involved with their new-borns. Various factors that came up during the analysis include bonding, the helper and supportive partner, and emotionally absent. These factors contributed to an emphasised need for paternity leave as participants narrated their experiences and challenges. With the implementation of paternity leave participants felt that ten days of leave provision in South Africa would be the first steps to moving towards gender equality in the workplace and strict measures need to be put in place to ensure that fathers do not misuse the paternity leave. The study recommends further research to be conducted on the mother’s perspective on paternity leave. It is also anticipated that the result may support the amendment of Basic Conditions of Employment Act, or develop progressive policy which can equally cater for both men and women in equal terms. Keywords: Basic Conditions of Employment Act, Paternity leave, Fatherhood, Family.
Keywords: Parental leave--South Africa; Employee rights--South Africa; Fatherhood--South Africa; Masculinity--South Africa